Ejemplo 1: Secciones cónicas (Parábola) - Solís-Palma, Angie (My University, 2018)
Determinar la ecuación canónica de una parábola a partir de ciertas condiciones y construir su gráfica.

Determine the canonical equation of a parabola from certain conditions and construct its graph.
Keywords: Secciones cónicas; Conic sections; Parábola; Cálculo de variables; Variable calculation; Calculus; Cálculo superior